2007
DOI: 10.1128/jvi.01008-07
|View full text |Cite
|
Sign up to set email alerts
|

Innate Recognition Network Driving Herpes Simplex Virus-Induced Corneal Immunopathology: Role of the Toll Pathway in Early Inflammatory Events in Stromal Keratitis

Abstract: Ocular infection with herpes simplex virus (HSV) sets off an array of events that succeed in clearing virus from the cornea but leaves the tissue with a CD4؉ T-cell-orchestrated chronic inflammatory lesion that impairs vision. We demonstrate that Toll-like receptor (TLR) signaling forms a part of the recognition system that induces the syndrome that eventually culminates in immunopathology. Accordingly, in a comparison of the outcomes of infection in wild-type (WT) mice and those lacking TLR function, it was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
100
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 43 publications
5
100
0
Order By: Relevance
“…However, in mice lacking functional TLR2, authors detected a blunted cytokine response or inflammatory infiltrates in the HSV-infected brain, but the mice did not have higher virus titers than wild-type (WT) counterparts, suggesting that TLR2 plays an important role in herpes encephalitis. Interestingly, similar observations have recently been made in a murine model of HSV eye infection (Sarangi et al, 2007). Moreover, a recent report also support a role for TLR2 signaling in HSV infection, which identified an association between naturally occurring polymorphisms in the human gene for TLR2 and the severity and recurrent infections of HSV-2 genital lesions and increased viral shedding in humans (Bochud et al, 2007), suggesting a role for TLR2 in the regulation of HSV-induced disease in the human population.…”
Section: Hsv and Tlr2supporting
confidence: 72%
See 1 more Smart Citation
“…However, in mice lacking functional TLR2, authors detected a blunted cytokine response or inflammatory infiltrates in the HSV-infected brain, but the mice did not have higher virus titers than wild-type (WT) counterparts, suggesting that TLR2 plays an important role in herpes encephalitis. Interestingly, similar observations have recently been made in a murine model of HSV eye infection (Sarangi et al, 2007). Moreover, a recent report also support a role for TLR2 signaling in HSV infection, which identified an association between naturally occurring polymorphisms in the human gene for TLR2 and the severity and recurrent infections of HSV-2 genital lesions and increased viral shedding in humans (Bochud et al, 2007), suggesting a role for TLR2 in the regulation of HSV-induced disease in the human population.…”
Section: Hsv and Tlr2supporting
confidence: 72%
“…However, the regulation of HSV-induced disease by TLR2 is not limited to models of HSV encephalitis, as TLR2 -/ -mice were also considerably resistant to ocular lesions associated with stromal keratitis caused by HSV-1 (Sarangi et al, 2007). Taken together, these data suggest that HSV infection detected by TLR2 resulted in an immoderate cytokine response that had lethal consequences for the host, although this is usually a protective mechanism.…”
Section: Hsv and Tlr2mentioning
confidence: 94%
“…145 Additionally, TLR4 is activated in mice by endogenous heat shock protein 70 (Hsp70) and β-defensin-3 expressed by corneal cells in response to the virus. 140 Interestingly, MyD88 − / − mice had reduced corneal inflammation, but were unable to control viral spread, with 70% dying of presumed HSV encephalitis.…”
Section: Onchocerca Volvulus (Onchocerciasis) Onchocerciasis Is Due Tmentioning
confidence: 99%
“…TLR2 − / − mice have been shown to have a decreased inflammatory response to infection, 139,140 whereas CpG sequences of HSV1 DNA are recognised stimulators of TLR9. 141,142 TLR3 recognises doublestranded RNA and has been identified as an important mediator of HSV1 infection.…”
Section: Onchocerca Volvulus (Onchocerciasis) Onchocerciasis Is Due Tmentioning
confidence: 99%
“…Studies in animal models of stromal keratitis (SK) 3 have revealed that the infection, possibly in part because of its TLR ligand activity, sets off a range of critical cellular and molecular events (1); the actual SK lesions, however, appear to be orchestrated mainly by CD4 ϩ T cells that are primarily type 1 cytokine producers (2,3). SK lesions may resolve spontaneously and, when this occurs in the mouse model, it may be associated with up-regulation of IL-10 production (4).…”
mentioning
confidence: 99%